THE EFFECT OF COMPANY SIZE, ASSET GROWTH, LEVERAGE, PRICE TO EARNINGS RATIO, PRICE TO BOOK VALUE AND STOCK PRICE VOLATILITY IN ISLAMIC COMPANIES LISTED ON IDX-MES BUMN 17 - Cika Dian Sastriavi; Rizky Fadhillah (ADISAM Publisher, 2025)
This study aims to examine the effect of company size, asset growth, leverage, price to earnings ratio, price to book value, and earnings volatility on stock price volatility in Sharia companies listed on the IDX MES BUMN 17 index. The research population with the results of 10 Sharia companies that match the criteria for purposive sampling on 17 companies listed on the IDX MES BUMN 17 for the period 2021-2024. Data analysis using warpPLS with testing on descriptive statistics, model fit, outer model, and inner model. The results showed that company size, asset growth, leverage, and price to earnings ratio had no significant effect on stock price volatility. Price to book value has a positive and significant effect on stock price volatility and earnings volatility has a negative and significant effect on stock price volatility. The R-square test results show an R-square value of 0.718, which means that together the variables of company size, asset growth, leverage, price to earnings ratio, price to book value, and earnings volatility have a significant effect on stock price volatility.